Psychotherapy training in Nepal: views of early career psychiatrists. (May 2021) - Rai, Yugesh; Karki, Utkarsh; Pinto da Costa, Mariana
Abstract : Although training in psychotherapy is an integral part of psychiatry training, standards in psychotherapy training have wide variation across and within countries. Post-graduate psychiatry training has been conducted in Nepal for over two decades, but little is known about its psychotherapy training provisions. An online survey was conducted with early career psychiatrists in Nepal. The findings show that the majority recognised psychotherapy training as important and were eager to pursue further training. However, two-thirds had no access to psychotherapy training opportunities. These results highlight the need to improve access to training in different psychotherapy modalities in Nepal.